Proteinuria and malaria parasite counts in children - Mahrani Lubis; Rusdidjas Rusdidjas; Rafita Ramayati; Oke Rina Ramayani; Rosmayanti S Siregar; Supriatmo Supriatmo (Indonesian Pediatric Society, 2013)
Background Malaria-induced proteinuria has been observed insevere cases of malaria. Few studies have been done to assess foran association between proteinuria and malaria parasite countsbefore the disease becomes severe.Objective To investigate a possible association between proteinuriaand malaria parasite counts in children .Methods A cross-sectional study was conducted on school-agedchildren in Panyabungan, Mandailing Natal, between Septemberto November 2010. Malaria was diagnosed by microscopicexamination of peripheral blood smears. Children with malariaunderwent proteinuria t ests by urine dipstick method. Anassociation between proteinuria and malaria parasite counts wasanalyzed using linear regression test.Results Of 181 participants with Plasmodium fak:iparum malaria,53.6% were female and had a mean age of 7.8 years. Subjects'nutritional status were as follows: 50.8% normoweight, 28.2%mild malnutrition, 3 .3% moderate malnutrition, and 17. 7% severemalnutrition. Clinical manifestations showed 36.5% suffered fromsubfebrile temperatures and 29.8% had pallor. Proteinuria occurredin 45.9% participants and there was a weak association betweenproteinuria and malaria parasite counts (raa .261, Paa .0001).Conclusion There is a weak association between proteinuria andmalaria parasite counts in children.